Integrating jigsaw teaching into self-regulated learning instruction: an instructional design to improve nursing students’ self-regulated learning - Chen, Yiwen; Song, Jiali; Li, Mengying; He, Huijuan; Wang, Xiangrong; Zhou, Siyu; Wang, Ling (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate the impact of integrating Jigsaw teaching into Self-regulated learning instruction on nursing students’ self-regulated learning ability and engagement.MethodsThis quasi-experimental study was conducted with 94 nursing students from Hubei University of Traditional Chinese Medicine (Hubei, China) in two classes during the fourth education semester. One classroom was assigned to the control group (43) and the other to the intervention group (50). In the course of Basic Nursing, the two classes adopted the traditional lecture teaching method and jigsaw teaching method to teach independent learning, respectively. The entire teaching scheme consisted of 12 class hours. The data collection tools were the self-regulated learning ability scale, the learning engagement scale, Self-assessment and mutual assessment forms. Data was collected before and after the interventions. Finally, data was analyzed by paired t-test, independent t-test and repeated measurement analysis of variance via SPSS 25.0 software.ResultsThe total scores of self-regulated learning ability and learning engagement of nursing students in the Intervention group were better than that of the control group (p < 0.05) before and after the educational intervention. The Self-assessment (F = 6.778, p < 0.001).and group mutual assessment of nursing students (F = 11.037, p < 0.001) in the Intervention group at three time points would show an increasing trend with prolonging the intervention time.ConclusionJigsaw teaching integrated with self-regulated learning can effectively enhance nursing students’ self-regulated learning ability and commitment, which is worth using in other nursing courses.